Interface modification compound for perovskite solar cell and novel cell structure
By using interface modification compounds containing triazine rings and cyano groups on the interface of perovskite solar cells, the defect state and energy level matching problem between the perovskite layer and the C60 electron transport layer is solved, and the performance and stability of the device are significantly improved.
Patent Information
- Application Number
- CN202510066359.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-29
AI Technical Summary
Interface problems of perovskite solar cells limit their performance improvement, especially the serious defect state and energy level matching between the perovskite active layer and the C60 electron transport layer, resulting in a decrease in open circuit voltage and fill factor.
Using an interface modification compound including a first structural unit of a triazine ring and a cyano group and a second structural unit of a phosphate or carboxylic acid group, a uniform interface modification layer is formed between the perovskite layer and the electron transport layer by spin coating and vacuum evaporation technology.
Effectively passivate perovskite surface defects, optimize the extraction and transmission of interface electrons, improve the open circuit voltage and photoelectric conversion efficiency of the device, and enhance the stability and durability of the film.
Smart Images

Figure CN119899211A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of perovskite solar cells, and in particular to an interface modification compound and a novel cell structure for perovskite solar cells. Background Art
[0002] Perovskite solar cells have attracted much attention in recent years due to their high photoelectric conversion efficiency and low-cost preparation process, but interface problems have significantly limited the further improvement of their performance. 60 The interface between the electron transport layer (ETL) often has serious defect states, such as uncoordinated Pb 2+ and I - Vacancies, etc. These defects will lead to increased interface carrier recombination, thus significantly reducing the open circuit voltage (Voc) and fill factor (FF) of the device. In addition, C 60 The poor energy level matching between the C and perovskite interfaces limits the efficient injection and transmission of electrons. More importantly, 60 Uneven coverage at the interface may induce leakage current, further compromising the stability of the device.
[0003] In the prior art, lithium fluoride (LiF) is often used as an interface layer by evaporation, and the required thickness is only 1nm, which places extremely high demands on the repeatability of the process. The limitation of equipment control accuracy leads to insufficient stability in the preparation of the interface layer, which is difficult to meet the needs of practical applications. Therefore, it is urgent to develop a thicker, more uniform and process-controllable interface modification material and deposition method to replace the existing LiF passivation layer and meet the high performance and high stability requirements of the industrialization of perovskite solar cells. Summary of the invention
[0004] The present application provides an interface modification compound and a novel battery structure for perovskite solar cells. The interface modification compound provided in the present application synthesizes a series of functionalized molecules containing carboxylic acid groups, phosphoric acid groups, cyano groups and azine rings, which are used for interface modification of perovskite layers and electron transport layers, and can form a uniform interface modification layer, thereby improving the performance and stability of perovskite batteries.
[0005] In a first aspect, the present application provides an interface modification compound for a perovskite solar cell, wherein the interface modification compound is used to prepare an interface modification layer of the perovskite cell, wherein the interface modification layer is disposed between the perovskite layer and the electron transport layer of the perovskite cell, and wherein the interface modification compound comprises a first structural unit and a second structural unit, wherein the first structural unit comprises a triazine ring and a cyano group, and the second structural unit comprises a phosphate group and a linking group, or wherein the second structural unit comprises a carboxylic acid group and the linking group, and the linking group is an organic group composed of carbon and hydrogen; and the first structural unit is connected to the phosphate group or the carboxylic acid group via the linking group.
[0006] In a second aspect, the present application provides a novel battery structure, comprising a substrate, a hole transport layer, a perovskite layer, an interface modification layer, an electron transport layer and an electrode layer, wherein the interface modification layer is prepared from the interface modification compound described in any one of the first aspects.
[0007] In a third aspect, the present application provides a method for preparing a perovskite battery, the method comprising: selecting ITO conductive glass or FTO conductive glass as a substrate, cleaning the substrate, and treating it with ultraviolet ozone for 15-30 minutes; using [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphoric acid self-assembled monolayer as a hole transport layer, dissolving the hole transport layer in ethanol to prepare a precursor solution, and coating the precursor solution on the substrate by spin coating, and annealing at 100°C after spin coating. 30 minutes; dissolving cesium iodide, lead iodide, cesium bromide, methylamine chloride and formamidine iodide in a mixed solvent of dimethyl sulfoxide and N,N-dimethylformamide to prepare a perovskite precursor solution; subsequently, forming a perovskite film on the hole transport layer by spin coating, and annealing; depositing a synthesized interface modification compound on the surface of the perovskite film by vacuum evaporation as an interface modification layer, with a deposition rate of 0.05-0.08nm / s and a thickness of 5-10nm; depositing C on the surface of the interface modification layer by vacuum evaporation 60 , as the electron transport layer, the deposition rate is 0.1-0.15nm / s, and the thickness is 20-30nm; a metal copper or metal silver electrode is vacuum evaporated on the electron transport layer, and the electrode thickness is 80-120nm.
[0008] It can be seen that the interface modification compound provided by the present application includes a first structural unit and a second structural unit, the first structural unit includes a triazine ring and a cyano group, the second structural unit includes a phosphate group and a linking group, or the second structural unit includes a carboxylic acid group and a linking group, and the linking group is an organic group composed of carbon and hydrogen; the first structural unit is connected to the phosphate group or the carboxylic acid group through the linking group, wherein the carboxylic acid and the phosphonic acid groups are connected to the uncoordinated Pb on the surface of the perovskite. 2 + ions form a strong chemical anchor bond, significantly passivate the surface defects of the perovskite, reduce non-radiative recombination losses, and thus effectively improve the open circuit voltage (Voc) and photoelectric conversion efficiency (PCE) of the device. The introduction of cyano groups not only provides the material with a higher electron affinity, but also can have a weak coordination effect with the perovskite surface, thereby optimizing the extraction of interface electrons and the transmission of electrons. In this application, an interface modification compound is used to form a stable and uniform interface modification layer between the perovskite layer and the electron transport layer, which solves the problems of interface defects, poor energy level matching, and poor film quality in the prior art. BRIEF DESCRIPTION OF THE DRAWINGS
[0009] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments are briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work. Among them,
[0010] Figure 1 The chemical formula of the interface modification compound provided in the examples of the present application;
[0011] Figure 2 A schematic diagram of the molecular structure of the interface modification compound provided in the examples of the present application;
[0012] Figure 3 A schematic diagram of a method for preparing a triazine compound containing a phosphate group provided in an embodiment of the present application;
[0013] Figure 4 A schematic diagram of a method for preparing a triazine compound containing a carboxylic acid group provided in an embodiment of the present application;
[0014] Figure 5 A schematic diagram of energy level distribution of each layer corresponding to the comparative examples and examples provided in the embodiments of the present application;
[0015] Figure 6 A schematic diagram of the structure of the perovskite battery provided in the embodiments and comparative examples of the present application;
[0016] Figure 7 A schematic diagram of a process for preparing a perovskite battery provided in an embodiment of the present application;
[0017] Figure 8 JV curves of the comparative examples and devices of Examples 1 to 8 provided in the embodiments of the present application;
[0018] Fig. 9 This is the outdoor stability monitoring curve of the comparative example and embodiment devices provided in the embodiments of the present application. DETAILED DESCRIPTION
[0019] The embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention.
[0020] In a first aspect of the present application, the present application provides an interface modification compound for a perovskite solar cell, wherein the interface modification compound is used to prepare an interface modification layer of the perovskite cell, wherein the interface modification layer is disposed between the perovskite layer and the electron transport layer of the perovskite cell, and wherein the interface modification compound comprises a first structural unit and a second structural unit, wherein the first structural unit comprises a triazine ring and a cyano group, and the second structural unit comprises a phosphate group and a linking group, or wherein the second structural unit comprises a carboxylic acid group and the linking group, and the linking group is an organic group composed of carbon and hydrogen; and the first structural unit is connected to the phosphate group or the carboxylic acid group via the linking group.
[0021] Among them, carboxylic acid (-COOH) or phosphonic acid (-PO(OH)2) groups bind to the uncoordinated Pb on the perovskite surface. 2+ The ions form a strong chemical anchor bond, significantly passivating the surface defects of the perovskite and reducing the non-radiative recombination loss, thereby effectively improving the open circuit voltage (Voc) and photoelectric conversion efficiency (PCE) of the device. The cyano group (-CN) increases the electron affinity and can also have a weak coordination effect with the perovskite surface, thereby optimizing the extraction of interfacial electrons and the transmission of electrons. The aromatic group or short-chain alkyl group further adjusts the energy level distribution of the molecule, making its LUMO energy level highly matched with the perovskite conduction band energy level, thereby achieving efficient electron transmission and effectively blocking hole migration and inhibiting interfacial recombination.
[0022] In addition, the hydroxyl (-OH) and phosphine oxide (-P=O) groups in the interface modification compound further stabilize the structure of the interface modification layer through hydrogen bonds or electrostatic interactions, while enhancing the adhesion to the perovskite surface and improving the stability of the film. The polar structures of carbon oxide (-CO) and phosphine oxide (-P=O) enhance the interaction between the molecule and the perovskite surface, thereby improving the stability and durability of the interface modification layer.
[0023] Through molecular design, the interface modification compound has good thermal stability and compatibility with the evaporation process, and can achieve uniform film formation at a lower temperature to form a dense interface modification layer structure. The uniformity and density of the film not only reduce the pinhole defects in the interface modification layer, but also further improve the long-term stability and weather resistance of the perovskite device. These characteristics make the materials in this application show great application potential in improving the performance of perovskite photovoltaic devices and promoting large-scale production.
[0024] In some embodiments, the first structural unit is 4,6-dicyano-1,3,5-triazine.
[0025] In some embodiments, the linker is empty, or the linker is not empty, and the linker includes one of an alkyl group and an aromatic group.
[0026] In some embodiments, the alkyl group includes one of an ethyl group and a butyl group, and the aromatic group includes a phenyl group.
[0027] In some embodiments, the chemical formula of the interface modification compound is as follows Figure 1 (a) and Figure 1 As shown in (b), wherein R is a connecting group.
[0028] In some embodiments, the interface modification compound includes one of 2-phosphono-4,6-dicyano-1,3,5-triazine (interface modification compound a), (2-(4,6-dicyano-1,3,5-triazine)ethyl)phosphonic acid (interface modification compound b), (2-(4,6-dicyano-1,3,5-triazine)butyl)phosphonic acid (interface modification compound c), (2-(4,6-dicyano-1,3,5-triazine)phenyl)phosphonic acid (interface modification compound d), 2-(4,6-dicyano-1,3,5-triazine)formic acid (interface modification compound e), 2-(4,6-dicyano-1,3,5-triazine)propionic acid (interface modification compound f), 2-(4,6-dicyano-1,3,5-triazine)pentanoic acid (interface modification compound g), and 2-(4,6-dicyano-1,3,5-triazine)benzoic acid (interface modification compound h). The molecular structure diagrams of the above-mentioned interface modification compounds are shown in Figure 2 Interfacial modification compound a- Figure 2 The interface modified compound h is shown in the figure.
[0029] In some embodiments, the linker is empty, and the preparation method of the interface modification compound is as follows: add cyanuric chloride, potassium cyanide (KCN), potassium carbonate (K2CO3), water or methanol (H2O / MeOH) into a round-bottom flask, under argon protection, heat the mixture and stir to react at 50-80°C for 4-8 hours, after the reaction is completed, extract the reaction mixture 3-4 times, combine the organic phases and dry and collect them in a conical flask to obtain 2-chloro-4,6-dicyano-1,3,5-triazine; add the obtained 2-chloro-4,6-dicyano-1,3,5-triazine and A acid, triethylamine (Et3N), and B compound into a round-bottom flask, under argon protection and reflux conditions, heat the mixture and stir to react at 60-80°C for 4-8 hours, after the reaction is completed, extract the reaction mixture 3-4 times, combine the organic phases and dry and collect them in a conical flask to obtain the interface modification compound;
[0030] Wherein, the A acid is an acidic compound corresponding to the carboxylic acid group or the phosphoric acid group contained in the second structural unit, the A acid includes phosphorous acid (H3PO3) or chloroacetic acid (ClCH2COOH), and the B compound includes dichloromethane (CH2Cl2) or methanol (MeOH).
[0031] In some embodiments, when the second structure includes a phosphate group, the A acid is phosphorous acid (H3PO3), the B compound is dichloromethane (CH2Cl2), and the interface modification compound is 2-phosphonic acid-4,6-dicyano-1,3,5-triazine; when the second structure includes a carboxylic acid group, the A acid is chloroacetic acid (ClCH2COOH), the B compound is methanol (MeOH), and the interface modification compound is 2-(4,6-dicyano-1,3,5-triazine)carboxylic acid.
[0032] In some embodiments, the linker is not empty, and the preparation method of the interface modification compound is as follows: cyanuric chloride, potassium cyanide (KCN), potassium carbonate (K2CO3), water or methanol (H2O / MeOH) are added to a round-bottom flask, and the mixture is heated and stirred at 50-80°C for 4-8 hours under argon protection. After the reaction is completed, the reaction mixture is extracted 3-4 times, and the organic phases are combined and dried and collected in a conical flask to obtain 2-chloro-4,6-dicyano-1,3,5-triazine; the obtained 2-chloro-4,6-dicyano-1,3,5-triazine and C x H y Br, tetrakis(triphenylphosphine)palladium (Pd(PPh3)4), potassium acetate (KOAc) and toluene are added to a round-bottom flask, the mixture is heated and stirred at 100°C for overnight reaction, after the reaction is completed, the reaction mixture is extracted 3-4 times, the organic phases are combined and dried and collected in a conical flask to obtain (2-(4,6-dicyano-1,3,5-triazine) linker) bromide; the obtained (2-(4,6-dicyano-1,3,5-triazine) linker) bromide and A acid, triethylamine (Et3N) and B compound are added to a round-bottom flask, under argon protection and reflux conditions, the mixture is heated and stirred at 60-80°C for 4-8 hours, after the reaction is completed, the reaction mixture is extracted 3-4 times, the organic phases are combined and dried and collected in a conical flask to obtain the interface modification compound;
[0033] Among them, the C x H y Br corresponds to the linking group, including bromoethane (C2H5Br), bromobutane (C4H9Br) or bromobenzene (C6H5Br); the A acid is an acidic compound corresponding to the carboxylic acid group or the phosphate group contained in the second structural unit, the A acid includes phosphorous acid (H3PO3) or chloroacetic acid (ClCH2COOH), and the B compound includes dichloromethane (CH2Cl2) or methanol (MeOH).
[0034] In some embodiments, when the second structure includes a phosphate group and the linker is an ethyl group, the C x H yBr is ethyl bromide (C2H5Br), the acid A is phosphorous acid (H3PO3), the compound B is dichloromethane (CH2Cl2), and the interface modification compound is (2-(4,6-dicyano-1,3,5-triazine)ethyl)phosphonic acid; when the second structure includes a phosphate group and the linking group is a butyl group, the C x H y Br is bromobutyl (C4H9Br), the acid A is phosphorous acid (H3PO3), the compound B is dichloromethane (CH2Cl2), the interface modification compound is (2-(4,6-dicyano-1,3,5-triazine)butyl)phosphonic acid; when the second structure includes a phosphate group and the linking group is a phenyl group, the C x H y Br is bromobenzene (C6H5Br), the acid A is phosphorous acid (H3PO3), the compound B is dichloromethane (CH2Cl2), and the interface modification compound is (2-(4,6-dicyano-1,3,5-triazine)phenyl)phosphonic acid; when the second structure includes the carboxylic acid group and the linking group is ethyl, the C x H y Br is ethyl bromide (C2H5Br), the acid A is chloroacetic acid (ClCH2COOH), the compound B is methanol (MeOH), and the interface modification compound is 2-(4,6-dicyano-1,3,5-triazine) propionic acid; when the second structure includes the carboxylic acid group and the linking group is butyl, the C x H y Br is bromobutyl (C4H9Br), the A acid is chloroacetic acid (ClCH2COOH), the B compound is methanol (MeOH), and the interface modification compound is 2-(4,6-dicyano-1,3,5-triazine)pentanoic acid; when the second structure includes the carboxylic acid group and the linking group is a phenyl group, the C x H y Br is bromobenzene (C6H5Br), the A acid is chloroacetic acid (ClCH2COOH), the B compound is methanol (MeOH), and the interface modification compound is 2-(4,6-dicyano-1,3,5-triazine)benzoic acid.
[0035] For specific implementation, please refer to Figure 3 and Figure 4 , the following are the synthesis steps of each interface modification compound:
[0036] Interface modification compound a: 2-phosphonic acid-4,6-dicyano-1,3,5-triazine, synthesis method see Figure 3In (a): (1) Cyanuric chloride (5 mmol), potassium cyanide (2 equivalents, 10 mmol, KCN), potassium carbonate (1 equivalent, 5 mmol, K2CO3), and water / methanol (70 mL, H2O / MeOH) were added to a round-bottom flask. Under argon protection, the mixture was heated and stirred at 50-80°C for 4-8 hours. After the reaction was completed, the reaction mixture was extracted 3-4 times, and the organic phases were combined and dried and collected in a conical flask. (2) The obtained 2-chloro-4,6-dicyano-1,3,5-triazine (3.5 mmol), phosphorous acid (1 equivalent, 3.5 mmol, H3PO3), triethylamine (10 mL, Et3N), and dichloromethane (70 mL, CH2Cl2) were added to a round-bottom flask. Under argon protection and reflux conditions, the mixture was heated and stirred at 60-80°C for 4-8 hours. After the reaction was completed, the reaction mixture was extracted 3-4 times, and the organic phases were combined, dried and collected in a conical flask to obtain an interface modification compound a: 2-phosphonic acid-4,6-dicyano-1,3,5-triazine.
[0037] Interface modification compound b: (2-(4,6-dicyano-1,3,5-triazine)ethyl)phosphonic acid, synthesis method see Figure 3In (b): (1) Cyanuric chloride (5 mmol), potassium cyanide (2 equivalents, 10 mmol, KCN), potassium carbonate (2 equivalents, 10 mmol, K2CO3), water / methanol (70 mL, H2O / MeOH) were added to a round-bottom flask. Under argon protection, the mixture was heated and stirred at 50-80°C for 4-8 hours. After the reaction was completed, the reaction mixture was extracted 3-4 times, and the organic phases were combined and dried and collected in a conical flask. (2) The obtained 2-chloro-4,6-dicyano-1,3,5-triazine (3.5 mmol), bromoethane (1 equivalent, 3.5 mmol, C2H5Br), tetrakis(triphenylphosphine)palladium (5%, 0.17 mmol, Pd(PPh3)4), potassium acetate (1 equivalent, 3.5 mmol, KOAc) and toluene (70 mL, Toluene) were added to a round-bottom flask. The mixture was heated and stirred at 100°C for overnight reaction. After the reaction is completed, the reaction mixture is extracted 3-4 times, and the organic phases are combined and dried and collected in a conical flask. (3) The obtained (2-(4,6-dicyano-1,3,5-triazine)ethyl)bromide (2.5mmol), phosphorous acid (1 equivalent, 2.5mmol, H3PO3), triethylamine (10mL, Et3N), and dichloromethane (70mL, CH2Cl2) are added to a round-bottom flask. Under argon protection and reflux conditions, the mixture is heated and stirred at 60-80°C for 4-8 hours. After the reaction is completed, the reaction mixture is extracted 3-4 times, and the organic phases are combined and dried and collected in a conical flask to obtain the interface modification compound b: (2-(4,6-dicyano-1,3,5-triazine)ethyl)phosphonic acid.
[0038] Interface modification compound c: (2-(4,6-dicyano-1,3,5-triazine)butyl)phosphonic acid, synthesis method see Figure 3In (c): (1) Cyanuric chloride (5 mmol), potassium cyanide (2 equivalents, 10 mmol, KCN), potassium carbonate (2 equivalents, 10 mmol, K2CO3), water / methanol (70 mL, H2O / MeOH) were added to a round-bottom flask. Under argon protection, the mixture was heated and stirred at 50-80°C for 4-8 hours. After the reaction was completed, the reaction mixture was extracted 3-4 times, and the organic phases were combined and dried and collected in a conical flask. (2) The obtained 2-chloro-4,6-dicyano-1,3,5-triazine (3.5 mmol), 4-bromobutane (1 equivalent, 3.5 mmol, C4H9Br), tetrakis(triphenylphosphine)palladium (5%, 0.17 mmol, Pd(PPh3)4), potassium acetate (1 equivalent, 3.5 mmol, KOAc) and toluene (70 mL, Toluene) were added to a round-bottom flask. The mixture was heated and stirred at 100°C for overnight reaction. After the reaction is completed, the reaction mixture is extracted 3-4 times, and the organic phases are combined and dried and collected in a conical flask. (3) The obtained (2-(4,6-dicyano-1,3,5-triazine)butyl)bromide (2.5mmol), phosphorous acid (1 equivalent, 2.5mmol, H3PO3), triethylamine (10mL, Et3N), and dichloromethane (70mL, CH2Cl2) are added to a round-bottom flask. Under argon protection and reflux conditions, the mixture is heated and stirred at 60-80°C for 4-8 hours. After the reaction is completed, the reaction mixture is extracted 3-4 times, and the organic phases are combined and dried and collected in a conical flask to obtain the interface modification compound c: (2-(4,6-dicyano-1,3,5-triazine)butyl)phosphonic acid.
[0039] Interface modification compound d: (2-(4,6-dicyano-1,3,5-triazine)phenyl)phosphonic acid, synthesis method see Figure 3In (d): (1) Cyanuric chloride (5 mmol), potassium cyanide (2 equivalents, 10 mmol, KCN), potassium carbonate (2 equivalents, 10 mmol, K2CO3), water / methanol (70 mL, H2O / MeOH) were added to a round-bottom flask. Under argon protection, the mixture was heated and stirred at 50-80°C for 4-8 hours. After the reaction was completed, the reaction mixture was extracted 3-4 times, and the organic phases were combined and dried and collected in a conical flask. (2) The obtained 2-chloro-4,6-dicyano-1,3,5-triazine (3.5 mmol), 4-bromobutane (1 equivalent, 3.5 mmol, C4H9Br), tetrakis(triphenylphosphine)palladium (5%, 0.17 mmol, Pd(PPh3)4), potassium acetate (1 equivalent, 3.5 mmol, KOAc) and toluene (70 mL, Toluene) were added to a round-bottom flask. The mixture was heated and stirred at 100°C for overnight reaction. After the reaction is completed, the reaction mixture is extracted 3-4 times, and the organic phases are combined and dried and collected in a conical flask. (3) The obtained (2-(4,6-dicyano-1,3,5-triazine)phenyl)bromide (2.5mmol), phosphorous acid (1 equivalent, 2.5mmol, H3PO3), triethylamine (10mL, Et3N), and dichloromethane (70mL, CH2Cl2) are added to a round-bottom flask. Under argon protection and reflux conditions, the mixture is heated and stirred at 60-80°C for 4-8 hours. After the reaction is completed, the reaction mixture is extracted 3-4 times, and the organic phases are combined and dried and collected in a conical flask to obtain the interface modification compound d: (2-(4,6-dicyano-1,3,5-triazine)phenyl)phosphonic acid.
[0040] Interface modification compound e: 2-(4,6-dicyano-1,3,5-triazine)carboxylic acid, synthesis method see Figure 4 In (e): (1) Cyanuric chloride (5 mmol), potassium cyanide (2 equivalents, 10 mmol, KCN), potassium carbonate (1 equivalent, 5 mmol, K2CO3), water / methanol (70 mL, H2O / MeOH) were added to a round-bottom flask. Under argon protection, the mixture was heated and stirred at 50-80°C for 4-8 hours. After the reaction was completed, the reaction mixture was extracted 3-4 times, and the organic phases were combined and dried and collected in a conical flask. (2) The obtained 2-chloro-4,6-dicyano-1,3,5-triazine (3.5 mmol), chloroacetic acid (1 equivalent, 3.5 mmol, ClCH2COOH), triethylamine (10 mL, Et3N), and methanol (70 mL, MeOH) were added to a round-bottom flask. Under argon protection and reflux conditions, the mixture was heated and stirred at 60-80°C for 4-8 hours. After the reaction was completed, the reaction mixture was extracted 3-4 times, and the organic phases were combined, dried and collected in a conical flask to obtain an interface modification compound e: 2-(4,6-dicyano-1,3,5-triazine)carboxylic acid.
[0041] Interface modification compound f: 2-(4,6-dicyano-1,3,5-triazine) propionic acid, synthesis method see Figure 4 In (f): (1) Cyanuric chloride (5 mmol), potassium cyanide (2 equivalents, 10 mmol, KCN), potassium carbonate (2 equivalents, 10 mmol, K2CO3), water / methanol (70 mL, H2O / MeOH) were added to a round-bottom flask. Under argon protection, the mixture was heated and stirred at 50-80°C for 4-8 hours. After the reaction was completed, the reaction mixture was extracted 3-4 times, and the organic phases were combined and dried and collected in a conical flask. (2) The obtained 2-chloro-4,6-dicyano-1,3,5-triazine (3.5 mmol), bromoethane (1 equivalent, 3.5 mmol, C2H5Br), tetrakis(triphenylphosphine)palladium (5%, 0.17 mmol, Pd(PPh3)4), potassium acetate (1 equivalent, 3.5 mmol, KOAc) and toluene (70 mL, Toluene) were added to a round-bottom flask. The mixture was heated and stirred at 100°C for overnight reaction. After the reaction is completed, the reaction mixture is extracted 3-4 times, and the organic phases are combined and dried and collected in a conical flask. (3) The obtained (2-(4,6-dicyano-1,3,5-triazine)ethyl)bromide (2.5mmol), chloroacetic acid (1 equivalent, 2.5mmol, ClCH2COOH), triethylamine (10mL, Et3N), and methanol (70mL, MeOH) are added to a round-bottom flask. Under argon protection and reflux conditions, the mixture is heated and stirred at 60-80°C for 4-8 hours. After the reaction is completed, the reaction mixture is extracted 3-4 times, and the organic phases are combined and dried and collected in a conical flask to obtain the interface modification compound f: 2-(4,6-dicyano-1,3,5-triazine)propionic acid.
[0042] Interface modification compound g: 2-(4,6-dicyano-1,3,5-triazine)pentanoic acid, synthesis method see Figure 4In (g): (1) Cyanuric chloride (5 mmol), potassium cyanide (2 equivalents, 10 mmol, KCN), potassium carbonate (2 equivalents, 10 mmol, K2CO3), water / methanol (70 mL, H2O / MeOH) were added to a round-bottom flask. Under argon protection, the mixture was heated and stirred at 50-80°C for 4-8 hours. After the reaction was completed, the reaction mixture was extracted 3-4 times, and the organic phases were combined and dried and collected in a conical flask. (2) The obtained 2-chloro-4,6-dicyano-1,3,5-triazine (3.5 mmol), bromobutyl (1 equivalent, 3.5 mmol, C4H9Br), tetrakis(triphenylphosphine)palladium (5%, 0.17 mmol, Pd(PPh3)4), potassium acetate (1 equivalent, 3.5 mmol, KOAc) and toluene (70 mL, Toluene) were added to a round-bottom flask. The mixture was heated and stirred at 100°C for overnight reaction. After the reaction is completed, the reaction mixture is extracted 3-4 times, and the organic phases are combined and dried and collected in a conical flask. (3) The obtained (2-(4,6-dicyano-1,3,5-triazine)butyl)bromide (2.5mmol), chloroacetic acid (1 equivalent, 2.5mmol, ClCH2COOH), triethylamine (10mL, Et3N), and methanol (70mL, MeOH) are added to a round-bottom flask. Under argon protection and reflux conditions, the mixture is heated and stirred at 60-80°C for 4-8 hours. After the reaction is completed, the reaction mixture is extracted 3-4 times, and the organic phases are combined and dried and collected in a conical flask to obtain the interface modification compound g: 2-(4,6-dicyano-1,3,5-triazine)pentanoic acid.
[0043] Interface modification compound h: 2-(4,6-dicyano-1,3,5-triazine)benzoic acid, synthesis method see Figure 4(h): (1) Cyanuric chloride (5 mmol), potassium cyanide (2 equivalents, 10 mmol, KCN), potassium carbonate (2 equivalents, 10 mmol, K2CO3), water / methanol (70 mL, H2O / MeOH) were added to a round-bottom flask. Under argon protection, the mixture was heated and stirred at 50-80°C for 4-8 hours. After the reaction was completed, the reaction mixture was extracted 3-4 times, and the organic phases were combined and dried and collected in a conical flask. (2) The obtained 2-chloro-4,6-dicyano-1,3,5-triazine (3.5 mmol), bromobenzene (1 equivalent, 3.5 mmol, C6H5Br), tetrakis(triphenylphosphine)palladium (5%, 0.17 mmol, Pd(PPh3)4), potassium acetate (1 equivalent, 3.5 mmol, KOAc) and toluene (70 mL, Toluene) were added to a round-bottom flask. The mixture was heated and stirred at 100°C for overnight reaction. After the reaction is completed, the reaction mixture is extracted 3-4 times, and the organic phases are combined and dried and collected in a conical flask. (3) The obtained (2-(4,6-dicyano-1,3,5-triazine)phenyl)bromide (2.5mmol), chloroacetic acid (1 equivalent, 2.5mmol, ClCH2COOH), triethylamine (10mL, Et3N), and methanol (70mL, MeOH) are added to a round-bottom flask. Under argon protection and reflux conditions, the mixture is heated and stirred at 60-80°C for 4-8 hours. After the reaction is completed, the reaction mixture is extracted 3-4 times, and the organic phases are combined and dried and collected in a conical flask to obtain the interface modification compound h: 2-(4,6-dicyano-1,3,5-triazine)benzoic acid.
[0044] The energy levels of the HOMO (highest occupied molecular orbital) and LUMO (lowest unoccupied molecular orbital) of the above interface modification compounds a to h are calculated, as shown in Table 1.
[0045] Table 1 shows various interface modification compounds and their HOMO and LUMO energy levels provided in the examples of this application.
[0046]
[0047]
[0048] See also Figure 5 , Figure 5 Schematic diagram of energy level distribution of each layer corresponding to the comparative examples and examples provided in the embodiments of the present application. Figure 5 (a) is a schematic diagram of the energy levels of each layer of the comparative example. Figure 5 (b) is a schematic diagram of energy levels of each layer of 8 examples provided in this application, Figure 5It is shown in the figure that by rationally designing the key structure, the interface modification compounds synthesized in this application show better energy level matching between the upper and lower layers than the existing compound LiF, which promotes the efficient extraction and transmission of electrons. In addition, compared with the electron transport layer, these interface modification compounds have a wider band gap, which can effectively prevent the migration of holes at the perovskite interface, thereby reducing carrier recombination and improving the overall performance of the device.
[0049] In the second aspect of the present application, the present application provides a perovskite battery, see Figure 6 , Figure 6 The schematic diagram of the structure of the perovskite battery provided in the embodiments and comparative examples of the present application is shown in FIG. Figure 6 The perovskite cell includes a substrate, a hole transport layer, a perovskite layer, an interface modification layer, an electron transport layer and an electrode layer, wherein: Figure 6 The interface modification layer in (a) is made of LiF. Figure 6 The interface modification layer in (b) is prepared from the interface modification compound described in any one of the first aspects.
[0050] In the third aspect of the present application, the present application provides a method for preparing a perovskite battery, see Figure 7 , Figure 7 A schematic flow chart of a method for preparing a perovskite battery provided in an embodiment of the present application, the method comprising the following steps S701 to S706:
[0051] Step S701, selecting ITO conductive glass or FTO conductive glass as a substrate, cleaning the substrate, and then treating it with ultraviolet ozone for 15-30 minutes;
[0052] Step S702, using a [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphoric acid self-assembled monolayer as a hole transport layer, dissolving the hole transport layer in ethanol to prepare a precursor solution, coating the precursor solution on the substrate by spin coating, and annealing at 100° C. for 30 minutes after the spin coating is completed;
[0053] Step S703, dissolving cesium iodide (CsI), lead iodide (PbI2), cesium bromide (CsBr), methylamine chloride (CH3NH3Cl) and formamidine iodide (CH(NH2)2I) in a mixed solvent of dimethyl sulfoxide (DMSO) and N,N-dimethylformamide (DMF) to prepare a perovskite precursor solution; then, forming a perovskite film on the hole transport layer by spin coating, and annealing;
[0054] Step S704, depositing a synthesized interface modification compound on the surface of the perovskite film by vacuum evaporation as an interface modification layer, with a deposition rate of 0.05-0.08 nm / s and a thickness of 5-10 nm;
[0055] Step S705, depositing C on the surface of the interface modification layer by vacuum evaporation 60 , as an electron transport layer, the deposition rate is 0.1-0.15nm / s and the thickness is 20-30nm;
[0056] Step S706: vacuum-evaporating a metal copper (Cu) or metal silver (Ag) electrode on the electron transport layer, with the electrode thickness being 80-120 nm.
[0057] In step S704, different interface modification compounds provided in the present application are used to form an interface modification layer on the surface of the perovskite film to test the photoelectric properties of the interface modification compounds.
[0058] The scheme of the present application is described below through specific embodiments. It should be noted that the following embodiments are only used to illustrate the present application and should not be regarded as limiting the scope of the present application.
[0059] Example 1
[0060] like Figure 6 The method for preparing the perovskite cell shown in (b) comprises the following steps:
[0061] Step 1: Use ITO (Indium Tin Oxide) or FTO (Fluorine Doped Tin Dioxide) conductive glass as the substrate, clean it, and treat it with ultraviolet ozone (UVO) for 15-30 minutes for use.
[0062] Step 2: Using MeO-2PACz ([2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphoric acid) self-assembled monolayer as the hole transport layer, dissolve it in ethanol to prepare a precursor solution (concentration 0.5 mg / ml). Spin coating the precursor solution on the substrate, and anneal at 100°C for 30 minutes after spin coating.
[0063] Step 3: Dissolve cesium iodide (CsI), lead iodide (PbI2), cesium bromide (CsBr), methylamine chloride (CH3NH3Cl) and formamidine iodide (CH(NH2)2I) in a mixed solvent of DMSO (dimethyl sulfoxide) and DMF (N,N-dimethylformamide) to prepare a perovskite precursor solution. Subsequently, a perovskite film is formed on the hole transport layer by spin coating and annealed.
[0064] Step 4: Deposit the synthesized 2-phosphonic acid-4,6-dicyano-1,3,5-triazine (DC-T-PA) on the surface of the perovskite film by vacuum evaporation as the interface modification layer of the perovskite, with a deposition rate of 0.05-0.08 nm / s and a thickness of 5-10 nm.
[0065] Step 5: Next, C is deposited on the surface of the DC-T-PA layer by vacuum evaporation. 60 (Fullerene C 60 ), as the electron transport layer, the deposition rate is 0.1-0.15nm / s, and the thickness is 20-30nm.
[0066] Step 6: Finally, vacuum evaporate a metal copper (Cu) or silver (Ag) electrode on the electron transport layer, and the electrode thickness is controlled at 80-120nm.
[0067] The device prepared using the compound of Example 1 has a Voc (open circuit voltage) of 1.13 V and a Jsc (short circuit current) of 23.43 mA / cm 2 , FF (fill factor) is 82.32%, and PCE (photovoltaic efficiency) is 21.58%.
[0068] Example 2:
[0069] like Figure 6 The method for preparing the perovskite cell shown in (b) comprises the following steps:
[0070] Step 1: Use ITO or FTO conductive glass as the substrate, clean it, and treat it with ultraviolet ozone for 15-30 minutes for use.
[0071] Step 2: Using MeO-2PACz self-assembled monolayer as the hole transport layer, dissolve it in ethanol to prepare a precursor solution (concentration 0.5 mg / ml). Spin-coat the precursor solution on the substrate and anneal at 100° C. for 30 minutes after spin coating.
[0072] Step 3: Dissolve CsI, PbI2, CsBr, CH3NH3Cl and CH(NH2)2I in a mixed solvent of DMSO and DMF to prepare a perovskite precursor solution. Subsequently, a perovskite film is formed on the hole transport layer by spin coating and annealing.
[0073] Step 4: Deposit synthesized (2-(4,6-dicyano-1,3,5-triazine)ethyl)phosphonic acid (DC-T-EPA) on the surface of the perovskite film by vacuum evaporation as an interface modification layer of the perovskite with a deposition rate of 0.05-0.08 nm / s and a thickness of 5-10 nm.
[0074] Step 5: Next, C is deposited on the surface of the DC-T-EPA layer by vacuum evaporation. 60 , as an electron transport layer, the deposition rate is 0.1-0.15nm / s and the thickness is 20-30nm.
[0075] Step 6: Finally, vacuum evaporate metal Cu or Ag electrode on the electron transport layer, and the electrode thickness is controlled at 80-120nm.
[0076] The device prepared using the compound of Example 2 has a Voc of 1.14 V and a Jsc of 23.36 mA / cm 2 , FF is 82.94% and PCE is 22.00%.
[0077] Example 3:
[0078] like Figure 6 The method for preparing the perovskite cell shown in (b) comprises the following steps:
[0079] Step 1: Use ITO or FTO conductive glass as the substrate, clean it, and treat it with ultraviolet ozone for 15-30 minutes for use.
[0080] Step 2: Using MeO-2PACz self-assembled monolayer as the hole transport layer, dissolve it in ethanol to prepare a precursor solution (concentration 0.5 mg / ml). Spin-coat the precursor solution on the substrate and anneal at 100° C. for 30 minutes after spin coating.
[0081] Step 3: Dissolve CsI, PbI2, CsBr, CH3NH3Cl and CH(NH2)2I in a mixed solvent of DMSO and DMF to prepare a perovskite precursor solution. Subsequently, a perovskite film is formed on the hole transport layer by spin coating and annealing.
[0082] Step 4: Deposit synthesized (2-(4,6-dicyano-1,3,5-triazine)butyl)phosphonic acid (DC-T-BPA) on the surface of the perovskite film by vacuum evaporation as an interface modification layer of the perovskite with a deposition rate of 0.05-0.08 nm / s and a thickness of 5-10 nm.
[0083] Step 5: Next, C is deposited on the surface of the DC-T-BPA layer by vacuum evaporation. 60 , as an electron transport layer, the deposition rate is 0.1-0.15nm / s and the thickness is 20-30nm.
[0084] Step 6: Finally, vacuum evaporate metal Cu or Ag electrode on the electron transport layer, and the electrode thickness is controlled at 80-120nm.
[0085] The device prepared using the compound of Example 3 has a Voc of 1.16 V and a Jsc of 24.11 mA / cm 2 , FF is 84.17% and PCE is 23.40%.
[0086] Example 4:
[0087] like Figure 6 The method for preparing the perovskite cell shown in (b) comprises the following steps:
[0088] Step 1: Use ITO or FTO conductive glass as the substrate, clean it, and treat it with ultraviolet ozone for 15-30 minutes for use.
[0089] Step 2: Using MeO-2PACz self-assembled monolayer as the hole transport layer, dissolve it in ethanol to prepare a precursor solution (concentration 0.5 mg / ml). Spin-coat the precursor solution on the substrate and anneal at 100° C. for 30 minutes after spin coating.
[0090] Step 3: Dissolve CsI, PbI2, CsBr, CH3NH3Cl and CH(NH2)2I in a mixed solvent of DMSO and DMF to prepare a perovskite precursor solution. Subsequently, a perovskite film is formed on the hole transport layer by spin coating and annealing.
[0091] Step 4: Deposit synthesized (2-(4,6-dicyano-1,3,5-triazine)phenyl)phosphonic acid (DC-T-PPA) on the surface of the perovskite film by vacuum evaporation as an interface modification layer of the perovskite with a deposition rate of 0.05-0.08 nm / s and a thickness of 5-10 nm.
[0092] Step 5: Next, C is deposited on the surface of the DC-T-PPA layer by vacuum evaporation. 60 , as an electron transport layer, the deposition rate is 0.1-0.15nm / s and the thickness is 20-30nm.
[0093] Step 6: Finally, vacuum evaporate metal Cu or Ag electrode on the electron transport layer, and the electrode thickness is controlled at 80-120nm.
[0094] The device prepared using the compound of Example 4 has a Voc of 1.11 V and a Jsc of 23.02 mA / cm 2 , FF is 81.33% and PCE is 20.59%.
[0095] Example 5:
[0096] like Figure 6 The method for preparing the perovskite cell shown in (b) comprises the following steps:
[0097] Step 1: Use ITO or FTO conductive glass as the substrate, clean it, and treat it with ultraviolet ozone for 15-30 minutes for use.
[0098] Step 2: Using MeO-2PACz self-assembled monolayer as the hole transport layer, dissolve it in ethanol to prepare a precursor solution (concentration 0.5 mg / ml). Spin-coat the precursor solution on the substrate and anneal at 100° C. for 30 minutes after spin coating.
[0099] Step 3: Dissolve CsI, PbI2, CsBr, CH3NH3Cl and CH(NH2)2I in a mixed solvent of DMSO and DMF to prepare a perovskite precursor solution. Subsequently, a perovskite film is formed on the hole transport layer by spin coating and annealing.
[0100] Step 4: Synthesized 2-(4,6-dicyano-1,3,5-triazine)carboxylic acid (DC-T-FA) is deposited on the surface of the perovskite film by vacuum evaporation as an interface modification layer of the perovskite, with a deposition rate of 0.05-0.08 nm / s and a thickness of 5-10 nm.
[0101] Step 5: Next, C is deposited on the surface of the DC-T-FA layer by vacuum evaporation. 60 , as an electron transport layer, the deposition rate is 0.1-0.15nm / s and the thickness is 20-30nm.
[0102] Step 6: Finally, vacuum evaporate metal Cu or Ag electrode on the electron transport layer, and the electrode thickness is controlled at 80-120nm.
[0103] The device prepared using the compound of Example 5 has a Voc of 1.14 V and a Jsc of 23.37 mA / cm 2 , FF is 82.33% and PCE is 21.86%.
[0104] Example 6:
[0105] like Figure 6 The method for preparing the perovskite cell shown in (b) comprises the following steps:
[0106] Step 1: Use ITO or FTO conductive glass as the substrate, clean it, and treat it with ultraviolet ozone for 15-30 minutes for use.
[0107] Step 2: Using MeO-2PACz self-assembled monolayer as the hole transport layer, dissolve it in ethanol to prepare a precursor solution (concentration 0.5 mg / ml). Spin-coat the precursor solution on the substrate and anneal at 100° C. for 30 minutes after spin coating.
[0108] Step 3: Dissolve CsI, PbI2, CsBr, CH3NH3Cl and CH(NH2)2I in a mixed solvent of DMSO and DMF to prepare a perovskite precursor solution. Subsequently, a perovskite film is formed on the hole transport layer by spin coating and annealing.
[0109] Step 4: Deposit synthesized 2-(4,6-dicyano-1,3,5-triazine) propionic acid (DC-T-PrA) on the surface of the perovskite film by vacuum evaporation as an interface modification layer of the perovskite, with a deposition rate of 0.05-0.08 nm / s and a thickness of 5-10 nm.
[0110] Step 5: Next, C is deposited on the surface of the DC-T-PrA layer by vacuum evaporation. 60 , as an electron transport layer, the deposition rate is 0.1-0.15nm / s and the thickness is 20-30nm.
[0111] Step 6: Finally, vacuum evaporate metal Cu or Ag electrode on the electron transport layer, and the electrode thickness is controlled at 80-120nm.
[0112] The device prepared using the compound of Example 6 has a Voc of 1.15 V and a Jsc of 23.66 mA / cm 2 , FF is 82.62% and PCE is 22.39%.
[0113] Example 7:
[0114] like Figure 6 The method for preparing the perovskite cell shown in (b) comprises the following steps:
[0115] Step 1: Use ITO or FTO conductive glass as the substrate, clean it, and treat it with ultraviolet ozone for 15-30 minutes for use.
[0116] Step 2: Using MeO-2PACz self-assembled monolayer as the hole transport layer, dissolve it in ethanol to prepare a precursor solution (concentration 0.5 mg / ml). Spin-coat the precursor solution on the substrate and anneal at 100° C. for 30 minutes after spin coating.
[0117] Step 3: Dissolve CsI, PbI2, CsBr, CH3NH3Cl and CH(NH2)2I in a mixed solvent of DMSO and DMF to prepare a perovskite precursor solution. Subsequently, a perovskite film is formed on the hole transport layer by spin coating and annealing.
[0118] Step 4: Deposit the synthesized 2-(4,6-dicyano-1,3,5-triazine)pentanoic acid (DC-T-PVA) on the surface of the perovskite film by vacuum evaporation as the interface modification layer of the perovskite, with a deposition rate of 0.05-0.08 nm / s and a thickness of 5-10 nm.
[0119] Step 5: Next, C is deposited on the surface of the DC-T-PVA layer by vacuum evaporation. 60 , as an electron transport layer, the deposition rate is 0.1-0.15nm / s and the thickness is 20-30nm.
[0120] Step 6: Finally, vacuum evaporate metal Cu or Ag electrode on the electron transport layer, and the electrode thickness is controlled at 80-120nm.
[0121] The device prepared using the compound of Example 7 has a Voc of 1.16 V and a Jsc of 24.07 mA / cm 2 , FF is 83.82% and PCE is 23.33%.
[0122] Example 8:
[0123] like Figure 6 The method for preparing the perovskite cell shown in (b) comprises the following steps:
[0124] Step 1: Use ITO or FTO conductive glass as the substrate, clean it, and treat it with ultraviolet ozone for 15-30 minutes for use.
[0125] Step 2: Using MeO-2PACz self-assembled monolayer as the hole transport layer, dissolve it in ethanol to prepare a precursor solution (concentration 0.5 mg / ml). Spin-coat the precursor solution on the substrate and anneal at 100° C. for 30 minutes after spin coating.
[0126] Step 3: Dissolve CsI, PbI2, CsBr, CH3NH3Cl and CH(NH2)2I in a mixed solvent of DMSO and DMF to prepare a perovskite precursor solution. Subsequently, a perovskite film is formed on the hole transport layer by spin coating and annealing.
[0127] Step 4: Deposit the synthesized 2-(4,6-dicyano-1,3,5-triazine)benzoic acid (DC-T-BA) on the surface of the perovskite film by vacuum evaporation as the interface modification layer of the perovskite, with a deposition rate of 0.05-0.08 nm / s and a thickness of 5-10 nm.
[0128] Step 5: Next, C is deposited on the surface of the DC-T-BA layer by vacuum evaporation. 60 , as an electron transport layer, the deposition rate is 0.1-0.15nm / s and the thickness is 20-30nm.
[0129] Step 6: Finally, vacuum evaporate metal Cu or Ag electrode on the electron transport layer, and the electrode thickness is controlled at 80-120nm.
[0130] The device prepared using the compound of Example 8 has a Voc of 1.10 V and a Jsc of 23.57 mA / cm 2 , FF is 81.11% and PCE is 20.87%.
[0131] Comparative Example:
[0132] like Figure 6 The method for preparing the perovskite cell shown in (a) comprises the following steps:
[0133] Step 1: Use ITO (Indium Tin Oxide) or FTO (Fluorine Doped Tin Dioxide) conductive glass as the substrate, clean it, and treat it with ultraviolet ozone (UVO) for 15-30 minutes for use.
[0134] Step 2: Using MeO-2PACz ([2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphoric acid) self-assembled monolayer as the hole transport layer, dissolve it in ethanol to prepare a precursor solution (concentration 0.5 mg / ml). Spin coating the precursor solution on the substrate, and anneal at 100°C for 30 minutes after spin coating.
[0135] Step 3: Dissolve cesium iodide (CsI), lead iodide (PbI2), cesium bromide (CsBr), methylamine chloride (CH3NH3Cl) and formamidine iodide (CH(NH2)2I) in a mixed solvent of DMSO (dimethyl sulfoxide) and DMF (N,N-dimethylformamide) to prepare a perovskite precursor solution. Subsequently, a perovskite film is formed on the hole transport layer by spin coating and annealed.
[0136] Step 4: LiF (lithium fluoride) is deposited on the surface of the perovskite film by vacuum evaporation as an electron transport layer with a deposition rate of 0.01-0.02 nm / s and a thickness of 1 nm.
[0137] Step 5: Deposit C on the passivated surface by vacuum evaporation 60 (Fullerene C 60 ), as the electron transport layer, the deposition rate is 0.1-0.15nm / s and the thickness is 20-30nm.
[0138] Step 6: Deposit dense SnO2 (tin dioxide) on the surface of the perovskite layer by atomic layer deposition (ALD) as a hole blocking layer. The deposition conditions are chamber temperature 85-110°C, rate 0.08-0.12nm / cycle, and thickness 15-30nm.
[0139] Step 7: Finally, vacuum evaporate a metal copper (Cu) or silver (Ag) electrode on the electron transport layer, and the electrode thickness is controlled at 80-120nm.
[0140] The device of the comparative example has a Voc of 1.08 V and a Jsc of 23.55 mA / cm 2 , FF is 81.34% and PCE is 20.55%.
[0141] The photoelectric performance parameters of the devices of Examples 1 to 8 and the comparative examples are summarized in Table 2, and the JV curves of the devices of the comparative examples and Examples 1 to 8 are shown in Table 2. Figure 8 The outdoor stability monitoring curves of the comparative examples and the embodiment devices are as follows: Fig. 9 As shown. The experimental results show that both the open circuit voltage (Voc) and the fill factor (FF) have been improved, indicating that the interface defects have been effectively passivated, and the optimization of the perovskite / electron transport layer interface has significantly improved the stability and performance of the device. Among them, the devices of Example 3 and Example 7 show the best photoelectric conversion efficiency and stability, which is mainly due to the excellent work function matching of the two interface modification compounds DC-T-BPA and DC-T-PVA and the effective passivation of interface defects.
[0142] Table 2 Comparative Example / Example Device Experimental Data
[0143]
[0144]
[0145] It can be seen that the interface modification compound provided by the present application includes a first structural unit and a second structural unit, the first structural unit includes a triazine ring and a cyano group, the second structural unit includes a phosphate group and a linking group, or the second structural unit includes a carboxylic acid group and a linking group, and the linking group is an organic group composed of carbon and hydrogen; the first structural unit is connected to the phosphate group or the carboxylic acid group through the linking group, wherein the carboxylic acid and the phosphonic acid groups are connected to the uncoordinated Pb on the surface of the perovskite. 2+The ions form a strong chemical anchor bond, significantly passivate the surface defects of the perovskite, reduce the non-radiative recombination loss, and thus effectively improve the open circuit voltage (Voc) and photoelectric conversion efficiency (PCE) of the device. The introduction of the cyanide group not only provides the material with a higher electron affinity, but also can have a weak coordination effect with the perovskite surface, thereby optimizing the extraction of interface electrons and the transmission of electrons. In this application, an interface modification compound is used to form a stable and uniform interface modification layer between the perovskite layer and the electron transport layer, which solves the problems of interface defects, poor energy level matching and poor film quality in the prior art.
[0146] Unless otherwise specified, all terms used in this application have the same meaning as those generally understood by those skilled in the art to which this application belongs. All patents and publications related to this application are incorporated herein by reference in their entirety. The term "comprising" or "including" is an open expression, i.e., including the content specified in this application, but does not exclude the content of other aspects.
[0147] In the description of this specification, the description with reference to the terms "one embodiment", "another embodiment", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment are included in at least one embodiment of the present application. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art can combine and combine the different embodiments or examples described in this specification and the features of different embodiments or examples, unless they are contradictory. In addition, it should be noted that in this specification, the terms "first" and "second" are used for descriptive purposes only and cannot be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated.
[0148] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change and modify the above embodiments within the scope of the present application.
Claims
1. An interface modification compound for perovskite solar cells, characterized in that: The interface modification compound is used to prepare the interface modification layer of the perovskite battery, and the interface modification layer is arranged between the perovskite layer and the electron transport layer of the perovskite battery. The interface modification compound includes a first structural unit and a second structural unit, the first structural unit includes a triazine ring and a cyano group, the second structural unit includes a phosphate group and a linking group, or the second structural unit includes a carboxylic acid group and the linking group, and the linking group is an organic group composed of carbon and hydrogen; The first structural unit is connected to the phosphate group or the carboxylic acid group through the linking group.
2. The interface modification compound according to claim 1, characterized in that The first structural unit is 4,6-dicyano-1,3,5-triazine.
3. The interface modification compound according to claim 2, characterized in that The linking group is empty, or the linking group is not empty, and the linking group includes one of an alkyl group and an aromatic group.
4. The interface modification compound according to claim 3, characterized in that The alkyl group includes one of ethyl and butyl, and the aromatic group includes phenyl. The interface modification compound includes one of 2-phosphono-4,6-dicyano-1,3,5-triazine, (2-(4,6-dicyano-1,3,5-triazine)ethyl)phosphonic acid, (2-(4,6-dicyano-1,3,5-triazine)butyl)phosphonic acid, (2-(4,6-dicyano-1,3,5-triazine)phenyl)phosphonic acid, 2-(4,6-dicyano-1,3,5-triazine)formic acid, 2-(4,6-dicyano-1,3,5-triazine)propionic acid, 2-(4,6-dicyano-1,3,5-triazine)pentanoic acid, and 2-(4,6-dicyano-1,3,5-triazine)benzoic acid.
5. The interface modification compound according to claim 4, characterized in that The linking group is empty, and the preparation method of the interface modification compound is as follows: Cyanuric chloride, potassium cyanide, potassium carbonate, water or methanol are added to a round-bottom flask. Under argon protection, the mixture is heated and stirred at 50-80° C. for 4-8 hours. After the reaction is completed, the reaction mixture is extracted 3-4 times, and the organic phases are combined, dried and collected in a conical flask to obtain 2-chloro-4,6-dicyano-1,3,5-triazine; The obtained 2-chloro-4,6-dicyano-1,3,5-triazine, acid A, triethylamine and compound B are added into a round-bottom flask, and the mixture is heated and stirred at 60-80° C. for 4-8 hours under argon protection and reflux conditions. After the reaction is completed, the reaction mixture is extracted 3-4 times, and the organic phases are combined, dried and collected in a conical flask to obtain the interface modification compound; The acid A is an acidic compound corresponding to the carboxylic acid group or the phosphoric acid group contained in the second structural unit, the acid A includes phosphorous acid or chloroacetic acid, and the compound B includes dichloromethane or methanol.
6. The interface modification compound according to claim 5, characterized in that When the second structure includes a phosphate group, the acid A is phosphorous acid, the compound B is dichloromethane, and the interface modification compound is 2-phosphonic acid-4,6-dicyano-1,3,5-triazine; When the second structure includes a carboxylic acid group, the acid A is chloroacetic acid, the compound B is methanol, and the interface modification compound is 2-(4,6-dicyano-1,3,5-triazine)carboxylic acid.
7. The interface modification compound according to claim 4, characterized in that The linking group is not empty, and the preparation method of the interface modification compound is as follows: Cyanuric chloride, potassium cyanide, potassium carbonate, water or methanol are added to a round-bottom flask. Under argon protection, the mixture is heated and stirred at 50-80° C. for 4-8 hours. After the reaction is completed, the reaction mixture is extracted 3-4 times, and the organic phases are combined, dried and collected in a conical flask to obtain 2-chloro-4,6-dicyano-1,3,5-triazine; The obtained 2-chloro-4,6-dicyano-1,3,5-triazine and C x H y Br, tetrakis(triphenylphosphine)palladium, potassium acetate and toluene are added into a round-bottom flask, the mixture is heated and stirred at 100°C for overnight reaction, after the reaction is completed, the reaction mixture is extracted 3-4 times, the organic phases are combined and dried and collected in a conical flask to obtain (2-(4,6-dicyano-1,3,5-triazine) linker)bromide; The obtained (2-(4,6-dicyano-1,3,5-triazine) linker) bromide, acid A, triethylamine, and compound B are added to a round-bottom flask, and the mixture is heated and stirred at 60-80° C. for 4-8 hours under argon protection and reflux conditions. After the reaction is completed, the reaction mixture is extracted 3-4 times, and the organic phases are combined, dried, and collected in a conical flask to obtain the interface modification compound; Among them, the C x H y Br corresponds to the linking group, including ethyl bromide, butyl bromide or bromobenzene; the A acid is an acidic compound corresponding to the carboxylic acid group or the phosphoric acid group contained in the second structural unit, the A acid includes phosphorous acid or chloroacetic acid, and the B compound includes dichloromethane or methanol.
8. The interface modification compound according to claim 7, characterized in that When the second structure includes a phosphate group and the linker is an ethyl group, the C x H y Br is ethyl bromide, the A acid is phosphorous acid, the B compound is dichloromethane, and the interface modification compound is (2-(4,6-dicyano-1,3,5-triazine)ethyl)phosphonic acid; When the second structure includes a phosphate group and the linker is a butyl group, the C x H y Br is butyl bromide, the acid A is phosphorous acid, the compound B is dichloromethane, and the interface modification compound is (2-(4,6-dicyano-1,3,5-triazine)butyl)phosphonic acid; When the second structure includes a phosphate group and the linking group is a phenyl group, the C x H y Br is bromobenzene, the A acid is phosphorous acid, the B compound is dichloromethane, and the interface modification compound is (2-(4,6-dicyano-1,3,5-triazine)phenyl)phosphonic acid; When the second structure includes the carboxylic acid group and the linking group is an ethyl group, the C x H y Br is ethyl bromide, the A acid is chloroacetic acid, the B compound is methanol, and the interface modification compound is 2-(4,6-dicyano-1,3,5-triazine)propionic acid; When the second structure includes the carboxylic acid group and the linking group is a butyl group, the C x H y Br is butyl bromide, the acid A is chloroacetic acid, the compound B is methanol, and the interface modification compound is 2-(4,6-dicyano-1,3,5-triazine)pentanoic acid; When the second structure includes the carboxylic acid group and the linking group is a phenyl group, the C x H y Br is bromobenzene, the A acid is chloroacetic acid, the B compound is methanol, and the interface modification compound is 2-(4,6-dicyano-1,3,5-triazine)benzoic acid.
9. A new battery structure, characterized in that: The invention comprises a substrate, a hole transport layer, a perovskite layer, an interface modification layer, an electron transport layer and an electrode layer, wherein the interface modification layer is prepared from the interface modification compound according to any one of claims 1 to 8.
10. A method for preparing a perovskite battery, characterized in that: The method comprises: ITO conductive glass or FTO conductive glass is selected as the substrate, the substrate is cleaned, and then treated with ultraviolet ozone for 15-30 minutes; Using a [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphoric acid self-assembled monolayer as a hole transport layer, dissolving the hole transport layer in ethanol to prepare a precursor solution, coating the precursor solution on the substrate by spin coating, and annealing at 100° C. for 30 minutes after spin coating; Dissolving cesium iodide, lead iodide, cesium bromide, methylamine chloride and formamidine iodide in a mixed solvent of dimethyl sulfoxide and N,N-dimethylformamide to prepare a perovskite precursor solution; subsequently, forming a perovskite film on the hole transport layer by spin coating, and annealing; An interface modification compound synthesized by vacuum evaporation is deposited on the surface of the perovskite film as an interface modification layer, with a deposition rate of 0.05-0.08 nm / s and a thickness of 5-10 nm; C is deposited on the surface of the interface modification layer by vacuum evaporation 60 , as an electron transport layer, the deposition rate is 0.1-0.15nm / s and the thickness is 20-30nm; A metal copper or metal silver electrode is vacuum evaporated on the electron transport layer, and the electrode thickness is 80-120 nm.